Mapping the spread of fluoroquinolone resistance: continued presence of non-susceptible Escherichia coli in broilers - Ringenier, Moniek; Boyen, Filip; Bogaerts, Bert; Gand, Mathieu; Vanneste, Kevin; De Keersmaecker, Sigrid C. J.; Chantziaras, Ilias; Ibrahim, Nelima; Devreese, Mathias; Dewulf, Jeroen (Frontiers in Veterinary Science, 2025)
IntroductionSustained resistance against fluoroquinolones (FQ), without the use of FQ in broilers, raises important questions about other possible factors contributing to the persistence in farms. Therefore, the current study investigates the prevalence of FQ non-susceptibility in Escherichia coli on broiler farms and examines the roles of day-old chicks, the farm environment, and the antimicrobial use (AMU) in the dynamics of the within-flock spread.MethodsOn 29 Belgian broiler farms, AMU was monitored, while environmental and day-old chick intestinal samples (day 0) were collected before their arrival. On days 3 and 36 of the production round, 30 cloacal swabs were taken per farm. In all samples, total E. coli and FQ non susceptible E. coli isolates were quantified by non-selective and FQ selective isolation. A selection of the isolates was analyzed using whole-genome sequencing to characterize their resistance and virulence-associated determinants and to investigate their phylogenetic relatedness using core-genome multi-locus sequence typing (cgMLST) and whole-genome single-nucleotide polymorphism (SNP) analysis.ResultsBefore entering the stable, day-old chicks carried FQ non-susceptible E. coli on 79.3% of the farms, while FQ non-susceptible E. coli were found in 48.3% of the sampled environments. According to cgMLST, identical FQ non-susceptible isolates were found on day 0 and 36, suggesting that FQ non-susceptible isolates present in the environment at the start of a production round or in day-old chicks, can remain present until slaughter, even when no FQs were used. Total AMU was positively correlated with the proportion of FQ non-susceptible E. coli [r = 0.42, 95% CI (0.06, 0.68), p = 0.03], often also multidrug-resistant, at the end of the production cycle.ConclusionThe continued presence of FQ non-susceptible E. coli in broiler farms is likely the result of both a historical contamination at the farm level and a continuous influx along the production chain. AMU contributes to the continued presence of FQ non-susceptible E. coli in broiler farms, but accounted for only a small proportion of the variability in FQ non-susceptibility in currently investigated farms. The role of certain virulence-associated genes in the persistence of FQ non-susceptible E. coli in broiler farms deserves more in-depth research.